(untitled) (KULT_online, 2009)
At the core of Sybille Krämer’s most recent monograph is the idea that media should be understood as archetypal messengers. This places media on a continuum with angels, viruses, psychoanalysts, and witnesses. Based on an exemplary analysis of these phenomena, the German media theorist develops a "message model" which, when applied to medial transference, reveals a process characterised by distance, heteronomy, thirdness, materialism, and indifference. Supplementing this with the opposing idea of a "trail" – which, sadly, is not given as much attention – Krämer demonstrates the applicability of her concept to other topics within the field of media studies.